1975
DOI: 10.1111/j.1432-1033.1975.tb04050.x
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Circular DNA from Mitochondrial-Enriched Fractions of Four Petite-Negative Yeasts

Abstract: Closed‐circular DNA has been isolated from mitochondrial‐enriched fractions from four petite‐negative' yeasts. Electron microscope analysis has shown in each case the presence of a large discrete size class of circular DNA greater than 6 μm in length and smaller heterodisperse circular DNA less than 6 μm. Length and molecular weight measurements of the large circular DNA are: Candida parapsilosis, 11.14 ± 0.45 μ and 23.1 × 106; Hansenula wingei, 8.22 ± 0.43 μm and 17.3 × 106; Kluyveromyces lactis, 11.44 ± 0.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In a separate study of circular DNA in another yeast, Torulopsis glabrata, we again found a class of non-mitochondrial molecules which had a length of 3.1 pm and a buoyant density of 1.709 g/cm3 (4). By analogy with the heavy satellite in S. cerevisiae it can be inferred that the 3.1 pm circular molecules-in this yeast code for ribosomal RNAs. Recently we have recommenced studying the 3 pm molecules because of their potential for mediating inter-species transfer of genes.…”
Section: Introductionmentioning
confidence: 85%
“…In a separate study of circular DNA in another yeast, Torulopsis glabrata, we again found a class of non-mitochondrial molecules which had a length of 3.1 pm and a buoyant density of 1.709 g/cm3 (4). By analogy with the heavy satellite in S. cerevisiae it can be inferred that the 3.1 pm circular molecules-in this yeast code for ribosomal RNAs. Recently we have recommenced studying the 3 pm molecules because of their potential for mediating inter-species transfer of genes.…”
Section: Introductionmentioning
confidence: 85%
“…Among different organisms, the mtDNA sizes are highly variable, ranging from the 5-Am circles of animals to the 30-Mm circles found in pea leaves (13,(34)(35)(36)(37)(38)(39)(40)(41)(42). However, this large variance in size does not necessarily imply that comparable differences in information content exist among these mtDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…According to established belief all known mitochondrial genomes in budding yeasts (with only two exceptions) consist of circular DNA molecules, which range in size from 19 kb in Candida (Torulopsis) glabrata, henceforth T.glabrata, to > 100 kb in Brettanomyces custersii (O'Connor et al, 1976;Hoeben and Clark-Walker, 1986). Copy number has been estimated to vary from 20 to 100 genome equivalents per cell, representing 5-20% of total cellular DNA (Dujon, 1981; Conrad and Newlon, 1982).…”
Section: Introductionmentioning
confidence: 99%